Scanning electron micrograph analysis of hypomineralized enamel in permanent first molars - B. JÄLEVIK, W. DIETZ, & J. G. NORÉN (Paediatric Dentistry, 2005)
The developmental dental defects of enamel can be classified as quantitative enamel hypoplasia or qualitative enamel hypomineralization.